MENUMBUHKEMBANGKAN SEMANGAT KEWIRAUSAHAAN SISWA MELALUI PELATIHAN BISNIS DI SMK PGRI DONOROJO KECAMATAN DONOROJO KABUPATEN PACITAN - Smita Catur Sudyantara; Mila Diana Sari; Susantriana Dewi (Jurnal Pengabdian Kepada Masyarakat, 2022)
Business training is one of prakerin implementation activity (industrial work practice) at SMK PGRI Donorojo during pandemic. This activity is expected to increase entrepreneurship spirit in understanding the business. Students gain additional insight to create business plan, running a business and grow a business. It can support the quality the improvement of human resources (HR) who are not only ready to work but are ready to be entrepreneur. With the concept of thinking about business, it will give student to make a choice in planning and run a business after graduation. The purpose of these activities is to increase knowledge and insight about entrepreneurship, provide motivation to develop self-competence, and awareness to create a strategy and recognize the future challenge. The method analysis use of training need based on activity. In fact, business training can provide insight and knowledge about entrepreneurship so that it can increase awareness to become an entrepreneur